Peran Locus of Control dalam Memoderasi Pengaruh Self Regulated Learning, Perfeksionisme dan Motivasi Berprestasi terhadap Prokrastinasi Akademik Mahasiswa - Rizki, Bagus Galin Dwi; Mudrikah, Saringatun (Business and Accounting Education Journal, 2023)
This research aims to determine the role of locus of control in moderating the influence of self-regulated learning, perfectionism, and achievement motivation on academic procrastination. This study uses a quantitative approach. The population in this study were students who were still active in the 2018 Economic Education study program, totaling 93 students. The sampling technique uses saturated samples. The data collection technique in this research uses questionnaires, and the data analysis method uses descriptive analysis and Moderated Regression Analysis (MRA). The research results show that self-regulated learning and achievement motivation have a negative effect on academic procrastination. Perfectionism has a positive effect on academic procrastination. Locus of control is able to moderate the influence of self-regulated learning and achievement motivation on academic procrastination.